Implementasi Layanan Bimbingan Konseling dalam Membentuk Karakter Peduli Sosial dan Percaya Diri Siswa di MIM PK Kartasura - .Sukamdani, Aditya, Dra. Ratnasari Diah Utami, M.Si (2017)
This study aims to describe (1) the implementation of guidance and counseling services in shaping the character of social care and confidence of students in PK Kartasura MIM. (2) Barriers guidance and counseling services in shaping the character of social care and confidence of students in PK Kartasura MIM. (3) The solution of barriers guidance and counseling services in shaping the character of social care and confidence of students in PK Kartasura MIM. This type of research is qualitative. Data collection techniques in this research is by interview, observation and documentation. Checking the validity of this data using triangulation of sources and techniques. The results showed that: (1) Implementation of guidance in shaping the character of social care and confidence MIM PK Kartasura among others: (a) The basic service includes: activities programmed, counseling implicit learning (b) planning services individually, includes career guidance, (c) responsive service, include: individual counseling / group and reward and punishment, (d) support system, (2) barriers that exist among others: (a) a lack of understanding of teachers, (b) differences in perception between teachers and parents, (c) the character of different students, (d) are not yet supporting infrastructure. (3) The solution to overcome these obstacles, among others: (a) guidance implemented homeroom with the direction of Professor BK, (b) provide flexibility consultation for parents, (c) the preparation of programs to fit the stage of development of students, (d) optimize existing facilities